A GENETIC ALGORITHM BASED METHOD FOR TIMETABLING PROBLEMS USING LINGUISTICS OF HEDGE ALGEBRA IN CONSTRAINTS - Long, Duong Thang (Journal of Computer Science and Cybernetics, 2017)
Timetabling problem is one of the very significant problems in many fields of applications. As mentioned in [6], this is an NP-complete of difficult problem which has many factors and complex constraints. In particular, this kind of problems usually has multiobjectives, so it is also in the multi-objectives optimization problem. Currently, in the educational institutions, especially higher education, the work scheduling was very difficult, especially in credits training. Sometimes we are very difficult to control all cases of the problem by human, thus effectively bringing not high yet. There have been many researchers offer methods to resolve this issue and in which search method based on genetic algorithms proved effective in many studies. This paper will study and propose a method based on genetic algorithms with hedge algebra fuzzy based constraint parameters and specific test at Hanoi Open University.